PENGARUH MODEL PEMBELAJARAN TGT DENGAN MEDIA LUDO TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS V SEKOLAH DASAR - Lilik Farikhah; Imaniar Purbasari; Wawan Shokib Rondli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by a learning system that is not yet innovative, the media is not very diverse, the lecture method makes students less active and shy when learning. The purpose of this study was to determine the effect of the TGT learning model assisted by ludo game media on learning outcomes in class V theme 8 sub-theme 1 SD Negeri Prawoto 02. This type of research is an experimental study with a One Group Pretest Posttest design. The research sample consisted of 24 students. The data analysis technique was statistical using SPSS 24 in the normality test using the Lilliefers test, homogeneity test using Levena Statistics, and paired sample t-test. The results of the normality test obtained sig values ​​of 0.151 and 0.062 > 0.05 indicating that the data were normally distributed and the results of the homogeneity test obtained sig values ​​of 0.335 > 0.05 indicating that the research data was homogeneous. The results of this study prove that the TGT learning model assisted by the ludo game media influences learning outcomes, namely the sig(2-tailed) value of 0.000 <0.05. The conclusion obtained is that there is a significant difference between pretest and posttest.